2021
DOI: 10.1186/s13018-021-02652-7
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and radiographic outcomes of hybrid graft in patients with Modic changes undergoing transforaminal lumbar interbody fusion

Abstract: Background This retrospective study aimed to analyze the influence of Modic changes (MCs) on the clinical and radiographic outcomes of transforaminal lumbar interbody fusion with hybrid graft. Methods Clinical data of 89 patients with Modic changes who underwent single-segment transforaminal lumbar interbody fusion between January 2015 and January 2019 at our institution were analyzed. Patients were divided into three groups: the MCs-0 group (no en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Nine studies evaluating lumbar fusion surgery were identified. One study evaluated oblique lateral interbody fusions (OLIF) [ 43 ], two evaluated transforaminal lumbar interbody fusions (TLIFs) [ 23 , 40 ], two included multiple fusion techniques [ 51 , 56 ], two evaluated PLIF [ 42 , 47 ], and two evaluated posterolateral fusions [ 48 , 58 ]. In general, patients had substantial improvements in the clinical outcomes and fusion rates regardless of the presence of MCs, with the exception of one study, which found decreased fusion rates and worse outcomes in patients with type III MCs [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies evaluating lumbar fusion surgery were identified. One study evaluated oblique lateral interbody fusions (OLIF) [ 43 ], two evaluated transforaminal lumbar interbody fusions (TLIFs) [ 23 , 40 ], two included multiple fusion techniques [ 51 , 56 ], two evaluated PLIF [ 42 , 47 ], and two evaluated posterolateral fusions [ 48 , 58 ]. In general, patients had substantial improvements in the clinical outcomes and fusion rates regardless of the presence of MCs, with the exception of one study, which found decreased fusion rates and worse outcomes in patients with type III MCs [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Jiao et al [ 40 ] retrospectively identified 89 patients, 51 with MC, who underwent single-level TLIFs. The authors found no difference in the fusion rate or clinical outcomes based on MCs, but type I MCs were associated with significantly higher rates of cage subsidence (40% to 15.8%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After stratification by MC subtype, nine studies were included that reported on leg pain in patients without Modic changes, 29,30,32,33,35,36,38,39,42 ten examined patients with MC-I, 29,30,32,33,35,36,38,39,41,42 and eight reported on leg pain in patients with MC-II. 29,30,32,33,36,39,41,42 Forest plots revealed a high degree of data heterogeneity (I 2 = 61%, P < .01). MC subtypes were not significantly associated with difference in VAS leg scores ( P = .38) (Supplemental Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Pooled reports of back pain intensity among patients with and without MC were reported in 10 studies. 24,[29][30][31][32][33][34][35][36][37][38][39] Low back pain intensity scores were standardized on a 0-10 scale. An initial funnel plot revealed possible publication bias in three studies 15,29,30 After these studies were excluded, a forest plot revealed low data heterogeneity (I 2 = 21%, P = .25) (Figure 2A).…”
Section: Visual Analogue Score Back Painmentioning
confidence: 99%